Examining the State's Jurisdiction in Sexual Assault Stateless Victims on Ships on the High Seas - Vidzal, Khaisya Refaya; Kusumo, Ayub Torry Satriyo; Indriyani, Rachma (Tirtayasa Journal of International Law, 2024)
Issues regarding jurisdiction over the handling of sexual assault cases, especially on the high seas, are a major concern of the international community, especially if the victim is a stateless person. They are often isolated and have limited access to legal assistance. This situation makes them one of the most vulnerable groups to sexual assault. The Stateless Convention 1954 stipulates that stateless persons can request legal protection from the state parties to the Convention. While on the high seas, UNCLOS 1982 has regulated that the flag state has jurisdiction over every activity on a ship flying its flag. However, there is no clarity regarding specific protection for stateless persons on ships. This paper will identify which jurisdictions can apply when there is a sexual assault against a stateless person on a ship on the high seas. The research method used is prescriptive normative law with a statute approach by examining laws and regulations. We argue that when it comes to ships flying a particular flag and sailing on the high seas, UNCLOS 1982 should be considered customary international law. Furthermore, when similar crimes occur, there must be a justification for intervention by other states. Scientific contributions in this study are the identification and juridical analysis of the legal gap in legal protection for stateless persons who are victims of sexual violence on the high seas, as well as a new interpretation of state jurisdiction based on the provisions of UNCLOS 1982 and the 1954 Stateless Convention.